Resource Isolating Mechanisms and Sustainable Competitive Advantage Among Commercial Banks in Kenya - Ndegwa, Purity W.; Kilika, James M.; Muathe, Stephen M. A. (European Scientific Journal, ESJ, 2018)
Kenyan commercial banks are facing intense rivalry within the industry due to dynamic changes in the external environment. For survival in the industry, it is important that banks respond to the changes in the external environment. Sustainable competitive advantage has become the core focus of corporate strategy, has increasingly gained much attention in strategic management and is a concept which enables organizations to survive in the long-run. The main purpose of this study was to establish the effect of resource isolating mechanism on sustainable competitive advantage among commercial banks in Kenya. The specific objectives in this study were to ascertain the effect of economic deterrence, identification of rival competitive advantage and exploitation of opportunities on sustainable competitive advantage among commercial banks in Kenya. Descriptive and explanatory research designs were employed in the study. The research targeted all the commercial banks in Kenya. Purposive sampling was used to select a sample of 160 respondents from the key departments of Finance, Sales and Marketing, Strategy and Operations of all the forty (40) commercial banks’ headquarters in Kenyan capital Nairobi. The data collection instrument used was semi-structured questionnaire. The variable characteristics were summarized using descriptive statistics. Agreement to the most frequent responses to the statements on the study variables ranged between moderate and high extent. Based on results of hypotheses testing, there exists a positive effect of resource isolating mechanism on sustainable competitive advantage.